2011
DOI: 10.1098/rsif.2011.0490
|View full text |Cite
|
Sign up to set email alerts
|

Statistical wall shear stress maps of ruptured and unruptured middle cerebral artery aneurysms

Abstract: Haemodynamics and morphology play an important role in the genesis, growth and rupture of cerebral aneurysms. The goal of this study was to generate and analyse statistical wall shear stress (WSS) distributions and shapes in middle cerebral artery (MCA) saccular aneurysms. Unsteady flow was simulated in seven ruptured and 15 unruptured MCA aneurysms. In order to compare these results, all geometries must be brought in a uniform coordinate system. For this, aneurysms with corresponding WSS data were transformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 44 publications
4
44
1
Order By: Relevance
“…Some studies revealed lower WSS on ruptured aneurysms than on asymptomatic unruptured ones. 5,7,16 A CFD study of hemodynamic differences between unruptured and ruptured IAs during observation has been reported recently. Thirteen aneurysms that ruptured during the course of follow-up observation were included in this study, and averaged WSS in the unruptured group was lower than in the rup- tured group in the MCA.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed lower WSS on ruptured aneurysms than on asymptomatic unruptured ones. 5,7,16 A CFD study of hemodynamic differences between unruptured and ruptured IAs during observation has been reported recently. Thirteen aneurysms that ruptured during the course of follow-up observation were included in this study, and averaged WSS in the unruptured group was lower than in the rup- tured group in the MCA.…”
Section: Discussionmentioning
confidence: 99%
“…The mean value averaged over 10 pulses at Re = 250 is found to be around 1.4 Pa with peak values near 2.6 Pa. At higher (possibly pathological) Reynolds number Re = 400 we observe a change in mean value up to 2.5 Pa and a considerable increase in peak values to 6.2 Pa averaged over 10 pulses. These values show the same general magnitude as reported in [29,70]. Transitional dynamics is clearly observed in Figure 4.5(b).…”
Section: Shear Stress Response In Normal and Pathological Flowsupporting
confidence: 73%
“…We consider a full range of physiologically relevant conditions and show that the flow undergoes a transition from an orderly state at low Reynolds numbers (Re = 100, 200), in which the pulsatile forcing is closely followed in time, to a complex response with strongly increased high-frequency components at higher Reynolds numbers (Re = 400), i.e., at higher flow rates and larger aneurysm sizes. The results obtained for the shear stress correspond to values found in literature [29,70], thereby providing an additional validation of the computational model. The numerical reliability of the predicted transition is quantified on the basis of the bounding solutions approach.…”
Section: Thesis Contentssupporting
confidence: 57%
“…Simulations have steadily migrated from idealized geometries to patient-specific IA geometries, from steady-state flow to pulsatile flow, and from qualitative flow pattern descriptions 20,22,23,43 to sophisticated quantitative statistical analyses. 4,5,30 Furthermore, efforts to bolster statistical power have increased the number of patient-specific IA cases per hemodynamic study from 1 (in the year 2003) 44 to 210 (in the year 2011). 5 Worldwide interactions between engineers and clinicians, exemplified by the annual International Intracranial Stent Meeting (http://www.ics-meeting.net), have stressed the dire medical need for clinically relevant information, including rupture risk assessments.…”
Section: Current Status Of Image-based Cfd Studies Of Aneurysmal Hemomentioning
confidence: 99%
“…5,30,31 Alternatively, some authors prefer to examine the spatial maximum (MWSS in Online Table 1) of TAWSS in an aneurysm. Both values require identification of the IA neck and an objective method to isolate the aneurysm.…”
Section: Wss In Aneurysm Developmentmentioning
confidence: 99%